‘Leave Your Ego at the Door’: A Narrative Investigation into Effective Wingsuit Flying - Arijs, Cedric; Chroni, Stiliani; Brymer, Eric; Carless, David (Frontiers in Psychology, 2017)
In recent years there has been a rapid growth in interest in extreme sports. For the most part research has focused on understanding motivations for participation in extreme sports and very little research has attempted to investigate the psychological structure of effective performance. Those few studies that have attempted to explore this issue have tested models designed for traditional sport on adventure sports. However, extreme sports are not the same as adventure sports or traditional sports. This study employed a narrative approach to investigate experiences of effective performance in the extreme sport of proximity wingsuit flying. An overarching theme we labelled ‘leave your ego at the door’, emerged based on four sub-themes: (1) know thy self, (2) know thy skills, (3) know the environment now, and (4) tame the ‘inner animal’. These themes are presented and discussed in relation to performance and discovery narratives identified within elite sport, thereby shedding light on how participants’ experiences of the extreme sport of proximity wingsuit flying differ from dominant stories within traditional sports.